Haematological effect of chlorfenapyr-exposed freshwater African mud catfish, Clarias gariepinus (Burchell 1822) - Imeh K. Esenowo; Maureen N. Chukwu; Akwaowo U. Nelson; Chibuisi G. Alimba; Micheal Johnson; Mmandu U. Effiong; Akaninyene U. Akpan; Adiaha A.A. Ugwumba; Nsima I. Udoidung; Nsikakabasi C. Ukpong; Alex O. Ugwumba; Efe Ogidiaka; Adeyemi O.A. Ale; Godsgift Sunday (Syiah Kuala University, 2023)
The effects of chlorfenapyr pesticide were investigated on juvenile of Clarias gariepinus. Sub-lethal test was carried out using 5, 7, 9, 11 and 15 mgL-1 of chlorfenapyr pesticide for 96 hours, and peripheral blood was collected through the caudal vein and examined for haematological changes. There was significant reduction (P0.05) in WBC when compared to the control. RBC increase was directly proportional to increase in chlorfenapyr dose and significantly differed from control (p0.05). HGB increased in a dose-dependent manner. MCV values of all treatment groups, except 15 mgL-1, were higher when compared to control. MCH was not significantly different from control. PLT decreased with increase in concentration and was lower for all treatment when compared with control. Results obtained in this study suggest that exposure to sub-lethal concentrations of chlorfenapyr can alter the haematological indices of non-target organisms.